Penerapan Modul Inventory Dalam Penyajian Laporan Persediaan Bahan Baku - Iriyadi, Iriyadi; Vimiyati, Kho (Institut Bisnis dan Informatika Kesatuan, 2013)
Inventory as one of major capital element stands its fuction to enhance business capability of aninterprise. A good inventory management, both administrative system and procurementmanagement, is one of decisive factors in view of the fact that inventory value is not insignificant.nventory management administratively consists of records and reports which can be presentedmanually and in simple way using excel. Nowadays, most enterprises record and maintain theirinventory by applying more enhanced and sophisticated computerized and integrated infrastructureprogram such as ERP (Enterprise Resources Planning) with the inventory module that facilitatesthe enterprise’s daily business activities, mainly the inventory including raw materials, work-inprocess, and finished goods. A good inventory management will secure the enterprise’s objectives,t without accurate and real-time information, it will risk not to meet the customers’ order.Considering the crucial role of inventory management to the enterprise’s business activities,the author performed the research concerning the implementation of inventory module in regard toaw material inventory report in PT Capsugel Indonesia. Raw material report consisting of firstbalance, income, expenditure, usage and last balance is essentially required by the management asupporting substance to make a good business and economic decision. It begins with procurementanalysis, deciding the time to issue purchasing order; managing delivery in order to meet safetyinventory level in warehouse and to keep the stock will not exceed the capacity of warehouse. Wellmanaged inventory includes managing procurement cost, storage cost as well as managing cashflow, will embrace the company’s objective to get profit.The author conducted the research on purchasing, warehouse, quality assurance, Productionand Finance & Accounting Department at PT Capsugel Indonesia located in Jl. Raya Bogor Km42, Cibinong. The research schedule was from April to July 2010.The result of the research shows that PT Capsugel Indonesia has implemented ERP(Enterprise Resources Planning) system named Mocrofoft Dynamics AX starting from purchasing,ceiving, dispositioning the status of inventory based on the income test result and distribution ofaw material. PT Capsugel Indonesia keeps both manual report of raw material inventory recordand report by system.The evaluation result indicates that the inventory module by system has been a goodinstrument for providing raw material inventory report, yet it is suggested that the system should beimplified in order to be communicative for better understanding.